Effect of winglet geometry on horizontal axis wind turbine performance. Issue 1 (21st January 2020) - Mourad, Mina G.; Shahin, Ibrahim; Ayad, Samir S.; Abdellatif, Osama E.; Mekhail, Tarek A.
Abstract : Winglets (WLs) have recently been used to improve the performance of horizontal axis wind turbine (HAWT). The WL geometry is a key parameter for diverging blade tip vortices away from turbine blades and reducing induced drag. The present study focuses on the effect of winglet height ( H ) and toe angle ( α w ) on the turbine performance. The performance of a three‐bladed rotor of 1 m diameter with SD8000 aerofoil is numerically investigated using ANSYS 17.2 CFD on a polyhedral mesh. The model is hence validated by comparing results for power coefficient ( C pw ) with experimental values available in the literature. Four different values of H are considered while keeping αw constant at 0°. H of 0.8% R is proved to be the best height for performance enhancement. It increases C pw by 2.4% at tip speed ratio λ  = 7. The toe angle effect is studied for upwind and downwind WLs. The results show that C pw increases as α w increases up to α w  = +20° at all values of λ . C pw increases by 6% at λ  = 7. Downwind WL always reduces C pw . The present results are well explained by the resulting vectors map near the blade tip. Using WL with the optimum H and α w, causes 6% increase in C pw as compared to rotor without WL. Abstract : To study the effect of winglet height, three different winglet heights are considered while keeping toe angle constant at 0°. Toe angle is studied for upwind and downwind winglets.